2012
DOI: 10.1093/toxsci/kfs154
|View full text |Cite
|
Sign up to set email alerts
|

Release of Apoptotic Cytochrome c From Mitochondria by Dimethylarsinous Acid Occurs Through Interaction With Voltage-Dependent Anion Channel In Vitro

Abstract: Arsenic is known to be a human carcinogen as well as one of the most effective drugs for treatment of patients with acute promyelocytic leukemia. The intermediate metabolites of arsenic, monomethylarsonous acid (MMA(III)) and dimethylarsinous acid (DMA(III)), are formed by methylation reactions, and they are more reactive and toxic than the inorganic precursor arsenite (iAs(III)); however, the detailed mechanism of toxicity is poorly understood. Here, we studied the effects of three arsenic compounds (i.e., iA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
1
20
1
Order By: Relevance
“…In the process of apoptosis triggered by the mitochondria-mediated signaling pathway, the opening of the PTP and subsequent perforation of the mitochondrial membrane decreases the ΔΨm and leads to the release of cytochrome c into the cytoplasm, were it activates caspases, which amplify the apoptotic signal and disassemble the cytoskeleton (31). The present study revealed that bufalin reduced the viability and induced apoptosis in the U-2OS human OS cell line in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 47%
“…In the process of apoptosis triggered by the mitochondria-mediated signaling pathway, the opening of the PTP and subsequent perforation of the mitochondrial membrane decreases the ΔΨm and leads to the release of cytochrome c into the cytoplasm, were it activates caspases, which amplify the apoptotic signal and disassemble the cytoskeleton (31). The present study revealed that bufalin reduced the viability and induced apoptosis in the U-2OS human OS cell line in a time-and dose-dependent manner.…”
Section: Discussionsupporting
confidence: 47%
“…Washed cell pellets (3 × 10 5 cells) were resuspended in protease buffer containing 10 mM Tris-buffer (pH 7.6), 1.5 mM MgCl 2 , 1 mM EDTA, 10 mM KCl, 1 mM phenylmethylsulphonyl fluoride (PMSF), and protease inhibitor tablets (contain 4-(2-aminoethyl) benzenesulfonyl fluoride (AEBSF), E-64, bestatin, leupeptin, aprotinin, and EDTA for inhibition of serine, cysteine, and metalloproteases). Whole cell extracts were prepared according to the published methods [14]. Briefly, MDA-MB-231 cells were washed once in cold PBS, followed by the cell pellets which were lysed by a single freeze-thaw cycle in the presence of protease inhibitors and whole cell extracts were obtained by centrifugation at 14000 rpm for 40 min after extraction with 0.5 M NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the proapoptotic protein Bax can increase the opening of VDAC by forming the Bax-VDAC complex or form a pore in the mitochondrial outer membrane on oligomerization (Narita et al 1998). In fact, there are two main pathways closely involved in the induction of Cyt c release from the mitochondria, a CsA-sensitive progress and a CsA-insensitive Bax-associated process (Naranmandura et al 2012;Weiss et al 2003); however, there is little information regarding which potential mPTP pathway is the main mediator of the release of Cyt c from the mitochondria during microbubble-assisted acoustic cavitation.…”
Section: Introductionmentioning
confidence: 99%